Organic Farming Strategy for Sustainable Food Production - Nisar A. Bhat (JOURNAL OF MANAGEMENT, SCIENCES, OPERATION & STRATEGIES, 2023)
Organic farming was once way of life around the world especially in India. It was, however, altered by modern agriculture especially the green revolution. Indigenous knowledge and local wisdom was ignored in adopting scientific approach, particularly in applying fertilizers. The Green Revolution Technologies’ led polluted ecosystems; depleted natural resources; lost biodiversity; less diverse diets; lost soil fertility/ soil fertility depletion; dependence on industrial inputs; imbalance/reduction in production; diminishing economic returns for farmers; increase in pesticide use; unscientific water management and distribution, and reduction in quality of the produce. All these problems of green revolution led to not only reduction in productivity but also deterioration of soil health as well as natural ecosystem. In India the commercial organic farming is still at a very nascent stage. About 528, 171 hectare area is under organic farming with 44,926 number of certified organic farms. This accounts for about 0.3 % of total agricultural land. Indian organic farming industry is estimated at US$ 78 million and is almost entirely export oriented. In the present article an attempt has been made to analyze the impact of Green Revolution Technologies’ on Indian agriculture, explore meaning, concept, importance and need of Organic Farming hence giving an impetus for adoption of an alternative farming system, may be the ‘Organic Farming’ for sustaining the productivity of the crop, disease resistance, maintaining the soil health and ensuring healthy ecosystems.